2018
DOI: 10.1080/03639045.2018.1496450
|View full text |Cite
|
Sign up to set email alerts
|

Development and in vitro evaluation of pH-independent release matrix tablet of weakly acidic drug valsartan using quality by design tools

Abstract: The main objective of this study was the development of pH-independent controlled release valsartan matrix tablet in Quality by design (QbD) framework. The quality target product profile (QTPP), critical quality attributes (CQAs) and critical material attributes (CMAs) were defined by science and risk-based methodologies. Potential risk factors were identified with Fishbone diagram. Following, CMAs were further investigated with a semi-quantitative risk assessment method, which has been revised with mitigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The Process Analytical Technology Framework (PAT), supported by the International Conference on Harmonization (ICH) provided the pharmaceutical industry sound practice over the years that has consolidated chemical, physical, microbiological, mathematical, risk assessment and regulatory insights to provide a navigation tool for strategic development and implementation of manufacturing and quality assurance. The salient features included are: a risk management and quality systems to maintain the quality of the system, access to latest technologies and developments, reviews and inspection activities, regulatory reflections and, health and safety (US FDA 2004;Orzechowski et al 2018;Saydam and Takka 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The Process Analytical Technology Framework (PAT), supported by the International Conference on Harmonization (ICH) provided the pharmaceutical industry sound practice over the years that has consolidated chemical, physical, microbiological, mathematical, risk assessment and regulatory insights to provide a navigation tool for strategic development and implementation of manufacturing and quality assurance. The salient features included are: a risk management and quality systems to maintain the quality of the system, access to latest technologies and developments, reviews and inspection activities, regulatory reflections and, health and safety (US FDA 2004;Orzechowski et al 2018;Saydam and Takka 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The ANOVA analysis revealed that at 20th hour polyethylene oxide was found to be the most influencing factor. An increase in the level of polyethylene oxide decreases drug release while cellulose acetate and polyethylene glycol are having no such effect [36].…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Post-compressional Parameters All factorial batches of the tablets were evaluated for official and unofficial test as per pharmacopoeia for weight variation, thickness, hardness and friability. 22,24,25 No Colour, shape and appearance are not directly linked to safety and efficacy. Therefore, they are not critical.…”
Section: Y= Bmentioning
confidence: 99%